2011
DOI: 10.1089/vbz.2010.0165
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological Survey of Hantavirus Infection in Healthy People in Vallès Occidental, Barcelona

Abstract: Our data show serological evidence about hantavirus infection among population of Catalonia, northeast of Spain. Seroprevalence rate was (around 2%) similar to other regions of Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…The 1.3% seroprevalence rate found in the present study is comparable to that seen in other central European countries (Sanfeliu et al 2011). In addition, a serosurvey of internal medicine patients in Austria in 1999 revealed closely similar results with an overall hantavirus seroprevalence of 1.2% (Aberle et al 1999).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The 1.3% seroprevalence rate found in the present study is comparable to that seen in other central European countries (Sanfeliu et al 2011). In addition, a serosurvey of internal medicine patients in Austria in 1999 revealed closely similar results with an overall hantavirus seroprevalence of 1.2% (Aberle et al 1999).…”
Section: Discussionsupporting
confidence: 88%
“…Second, screening was performed solely for PUU hantavirus, which is the only serotype detected in Austria so far, and did not include other serotypes like Dobrava-Belgrade virus (DOBV). Taking into account that DOBV is present in some of the countries where volunteers were employed, we cannot exclude possible cross-reactions from antigenically similar hantavirus serotypes, as demonstrated by Sanfeliu and associates (Sanfeliu et al 2011). However, Hukic and colleagues have shown that in endemic regions in Bosnia-Herzegovina the prevalence of DOBV (1.1%) is much lower than the prevalence of PUU hantavirus (5.1%) (Hukic et al 2010).…”
Section: Poeppl Et Almentioning
confidence: 99%
“…SEOV virus has been detected in Norway rats from Asia, Europe, and the Americas (Sanfeliu et al 2011), including Brazil (LeDuc et al 1985. However, laboratory-confirmed human cases outside of Asia are not frequent (Sanfeliu et al 2011), and few cases have been reported in Brazil (Clement et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Hantaviruses (family Bunyaviridae) are the etiological agents of different clinical syndromes, like hemorrhagic fever [4,5]. Although rodents were thought to be the main disease reservoir, recent studies from Côte d’Ivore and Gabon have provided evidence of shrew-borne hantavirus infections in humans [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that, in Spain, there is more than one genotype of hantavirus [7]. Certainly, hantaviruses have long been present in the Spanish regions of Catalonia [5] and Madrid (center) [7], as well as in the more northerly province of Soria [4].…”
Section: Introductionmentioning
confidence: 99%